Proverbial Expressions in Contextual Definition of Káà and its Postproverbial Imagination - Michael Olaniyi Ajadi (Yoruba Studies Review)
Káà is an architectural term widely used by the Yoruba to describe designative points in a radius of curvature for a building complex agbo-ilé. The general idea of this time-honored complex has based on combining apartments into a congruous unit to give central area/courtyard aya-ilé, strewn with sand for open-air entertainments, contests, spectacles and judicatory. As significant as this architectural term and design is to Yoruba social history, discourse that surrounds the conception vis-à-vis the proverbial and post proverbial expressions in terms of usages have not been studied to give in detail, the set of facts and circumstances that prompts their context of use. Structures and styles of diverse Yorùbá historical architectures with their constituent parts demand contextual examination in order to make clear definitions of each section in the complex and explicate its signification to the value system. An in-depth study of Yorùbá architectural designs will provide sectional scrutiny of each spatial location in their building complexes and unveil the social group’s time-honored customs. The paper, therefore, studies spatial attributes, styles, and designative units in diverse Yorùbá architectural structures for historical values and denotations of customary beliefs and practices. In-depth interviews and historical review methodologies were used for age-long structures of this style; pictures were taken for value orientation discussions and detailed analysis of each unit to ethical codes. Findings revealed the methodical and efficient sectional arrangement of the structures and affirmed that moral principles and cultural values are preserved in this social unit. However, the architectural styles have been a virile preservation of Yorùbá cultural heritage as a gregarious ethnic group who avoids solitude.